2016
DOI: 10.1097/01.ogx.0000489576.69844.54
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Betamethasone for Women at Risk for Late Preterm Delivery

Abstract: Background-Infants born at 34 to 36 weeks' gestation (late preterm) have greater risks of adverse respiratory and other outcomes, than those born at 37 weeks gestation or later. It is not known whether betamethasone administered to women at risk for late preterm delivery decreases risks of neonatal morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
253
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(272 citation statements)
references
References 6 publications
11
253
1
7
Order By: Relevance
“…Maternal hyperglycemia will cause hypoglycemia in newborns, which increased from 15% to 24% in a trial of ACS for late preterm pregnancies. 25 In low resource environments, newborn hypoglycemia may not be effectively monitored or treated, and may cause neurodevelopmental injury. 26,27 Short-term use of oral corticosteroids is frequent worldwide with underappreciated risks of sepsis, venous thrombosis, and fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal hyperglycemia will cause hypoglycemia in newborns, which increased from 15% to 24% in a trial of ACS for late preterm pregnancies. 25 In low resource environments, newborn hypoglycemia may not be effectively monitored or treated, and may cause neurodevelopmental injury. 26,27 Short-term use of oral corticosteroids is frequent worldwide with underappreciated risks of sepsis, venous thrombosis, and fracture.…”
Section: Discussionmentioning
confidence: 99%
“…20 Keeping with our results, a recent study in 2016 by Gyamfi-Bannerman and colleagues confirmed that administration of betamethasone to women at 34-36 weeks gestation significantly reduced the rate of TTN and surfactant use. 21 The main strength of the current study was the use of dexamethasone which is inexpensive, has no major side effects or complications, and has proven benefits. The large sample size of included women in the current study is another merit.…”
Section: Dexamethasone Before Elective Cesarean Section At Termmentioning
confidence: 99%
“…Furthermore, recent study indicated that antenatal corticosteroids are also effective in late preterm neonates (between 34 to 36 weeks) (29). The caesarean section rate was high comparing to WHO recommendation to be between 10-15% (30), controversially majority of the babies who died in this study were born by caesarian section compared to those born by normal delivery.…”
Section: Mother's Related Factorsmentioning
confidence: 78%